Controversial Issues in Enforcement of Human Right Between Islam and West - Ansori, Isa; ., Fauzan (KALAM, 2022)
Controversy over several human rights issues between Islamic and Western human rights activists is still happening. Some of the controversial issues that are often be debated are Qiṣāṣ, Ḥudūd, and women's rights. The question in this research is how human rights activists from both Muslim and Western view the practice of implementing Qiṣāṣ, Ḥudūd, and women's rights in the Muslim world. This paper focuses on describing the controversy between Muslim and Western human rights activists in upholding human rights especially related to the Qisas, Hudud, and women's rights issues. This is library research with a qualitative descriptive method. Data were analyzed using the inductive method. The results of the research showed that according to Western human rights activists, the enforcement of Islamic law in these three issues is contrary to the human rights values which are universally recognized. Meanwhile, in addressing these issues Muslim human rights activists are divided into two groups. The first is the textual group. This group views the necessity to apply Islamic law exactly as stated in the al-Qur'an and Hadith texts. Second, a group that is more moderate and even liberal. This group sees the need to reinterpret the text of the Koran and Hadith to make it more in line with the development of civilization. However, the two groups of Islamic human rights activists agree that Islamic law respects protects, and upholds human rights.